2015
DOI: 10.1111/1365-2435.12569
|View full text |Cite
|
Sign up to set email alerts
|

Functional correlations between specific leaf area and specific root length along a regional environmental gradient in Inner Mongolia grasslands

Abstract: Summary Among above‐ and below‐ground traits, specific leaf area (SLA, cm2 g−1) and specific root length (SRL, m g−1) are the two key traits reflecting species resource acquisition strategies. However, patterns of variation in SLA and SRL have rarely been examined simultaneously across evolutionary history and environmental gradients, and the SLA–SRL relationship is still controversial on several grounds. We examined the inter‐ and intraspecific variations in SLA and SRL of different root branching orders an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 56 publications
2
70
0
1
Order By: Relevance
“…For example, de Vries et al () observed CWM SLA to vary from 17.6 to 35.1 mm 2 /mg for a range of grassland types across England, while Grigulis et al () recorded a range in CWM SLA from 5 to 25 mm 2 /mg across montane grasslands in three geographically distinct locations in Europe. Furthermore, across a 2000‐km regional transect in Inner Mongolia, Cheng, Chu, Chen, Bai, and Niu () measured a breadth of variation in CWM SRL from 1 to 91 m/g. As such, the gradients of trait variation in our field communities were reasonably representative of those found in other studies at much larger scales, thereby enabling us to test our hypotheses on links between above‐ and below‐ground traits, soil properties and ecosystem C fluxes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, de Vries et al () observed CWM SLA to vary from 17.6 to 35.1 mm 2 /mg for a range of grassland types across England, while Grigulis et al () recorded a range in CWM SLA from 5 to 25 mm 2 /mg across montane grasslands in three geographically distinct locations in Europe. Furthermore, across a 2000‐km regional transect in Inner Mongolia, Cheng, Chu, Chen, Bai, and Niu () measured a breadth of variation in CWM SRL from 1 to 91 m/g. As such, the gradients of trait variation in our field communities were reasonably representative of those found in other studies at much larger scales, thereby enabling us to test our hypotheses on links between above‐ and below‐ground traits, soil properties and ecosystem C fluxes.…”
Section: Discussionmentioning
confidence: 99%
“…Wild ancestors displayed more correlations, particularly between root and leaf traits, than the domesticated forms. This result suggests that domestication and breeding may have consciously or unconsciously decoupled the different aspects of resource capture and use in modern varieties (Cheng, Chu, Chen, & Bai, ; Geng, Wang, Jin, Liu, & He, ). On the contrary, plant height, which was not related to the global strategy of the wild ancestor, was related to traits from the leaf economics spectrum and biomass production, from the first step of the domestication ( T. turgidum ssp.…”
Section: Discussionmentioning
confidence: 99%
“…The typical steppe, located at the middle part of the transect (sites 4–7), is dominated by Stipa grandis , L. chinensis and C. squarrosa . The desert steppe, located at the west part of the transect (sites 8–10), is dominated by S. krylovii , Cleistogenes songorica , S tipa breviflora , Zygophyllum gobicum , Halogetong lomeratus and Agropyron desertorum (Cheng, Chu, Chen, & Bai, ). Following a simple vegetation survey (Table S3), two regionally common species, grass L. chinensis and forb A. frigida , were selected to explore the intraspecific variation of root traits along the precipitation gradients.…”
Section: Methodsmentioning
confidence: 99%